Databanks in a Free Society / Computers, Record - Keeping and Privacy - Baker Michael A.; Westin Alan F (Quadrangle Books, 1972)
The first in-depth study of how computers are being used by corporations, government agencies and other record keepers to process information about people - what the effect on civil liberties has been, and what steps we can begin to take better protect personal privacy in record systems. Foreword, Preface, Records and Computers and Civil Liberties: The Setting of the Issues, Profiles from the World of Computerizing Organizations, Government Organizations: The Federal Level, Commercial Organizations, Nonprofit Organizations, Site - Visit Findings from 55 Advanced Systems, Future Directions in Computer Technology, Implications for Public Library, Appendices, Index.